2015
DOI: 10.3109/00365513.2014.993697
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of eight different D-dimer tests for the exclusion of deep venous thrombosis in primary care patients

Abstract: D-dimer tests are an essential element in the diagnostic work-up of deep venous thrombosis (DVT). However, the poor standardization amongst assays necessitates clinical validation before implementation in daily practice. We therefore evaluated the analytical and diagnostic performance of eight D-dimer tests in a representative group of 290 prospectively identified consecutive primary care patients with suspected DVT. Seven quantitative D-dimer assays, and a qualitative test, Simplify, were evaluated. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…whilst others recommend only citrate anticoagulated blood (e.g. [38]. Schutgens et al observed a higher mean D-dimer concentration (Tina-quant V R D-dimer) in heparin collection tubes (2510 mg/L), compared to citrate (2060 mg/L) albeit the difference did not achieve statistical significance [39].…”
Section: Anticoagulant Sample (Or Tube Additive)mentioning
confidence: 99%
See 2 more Smart Citations
“…whilst others recommend only citrate anticoagulated blood (e.g. [38]. Schutgens et al observed a higher mean D-dimer concentration (Tina-quant V R D-dimer) in heparin collection tubes (2510 mg/L), compared to citrate (2060 mg/L) albeit the difference did not achieve statistical significance [39].…”
Section: Anticoagulant Sample (Or Tube Additive)mentioning
confidence: 99%
“…This assay displayed sensitivity and specificity similar to those of microplate ELISAs, with the great advantage of being automated, thus generating more precise results in a shorter time (30 min) [3,58]. The Vidas V R assay is still considered the reference commercial quantitative immunoassay [84][85][86] and is the most clinically validated D-dimer measurement technique [38,48,85,[87][88][89].…”
Section: Analytical Variables D-dimer Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all were contemporary, well-validated high-sensitive quantitative D-dimer assays with similar fixed cut-off levels. 29 Based on our results, we conclude that use of statins is associated with a 15% decrease in D-dimer levels. In our cohort, this was not associated with an increase in falsenegative test results, compared to nonusers.…”
Section: Discussionmentioning
confidence: 57%
“…Evidences obtained in both surveys underline the need for further standardization in D-dimer result reporting. In general, D-dimer testing lacks standardization all over the world since there is still no standardized measurement unit, unique monoclonal antibody and calibrator ( 32 , 33 ). Thus results, RI and clinical cut-off values cannot be extrapolated between methods.…”
Section: Discussionmentioning
confidence: 99%